Resection of large hepatocellular carcinoma (≥10 cm): A unique western perspective. Issue 2 (17th August 2012) - Shrager, Brian; Jibara, Ghalib A.; Tabrizian, Parissa; Schwartz, Myron E.; Labow, Daniel M.; Hiotis, Spiros
Abstract Background and Objectives Few Western centers have surgically treated a high volume of large hepatocellular carcinoma 10 cm or more in diameter. The study aim was to analyze a large Western cohort of these patients, and to present our outcomes in the context of the more extensive Eastern experience. Methods We retrospectively reviewed all patients at our center receiving partial hepatectomy from January 1992 to August 2010, and analyzed a cohort with hepatocellular carcinoma ≥10 cm in diameter. Results One hundred thirty patients comprised the cohort. One hundred three (79.2%) of the patients received major anatomic resections, and 23 (17.7%) patients underwent tumor thrombectomy as an adjunct procedure. Perioperative mortality was observed in 9 (6.9%) of cases, but from January 2002 onward, only 2 (2.3%) of the 86 resections performed resulted in a mortality. The survival rate at 1, 3, and 5 years was 56.9%, 30.3%, and 18.8%, respectively; the median survival was 17.0 months. The subgroup of 39 patients without gross vascular invasion and satellite nodules achieved a median survival of 40.3 months. Conclusions Resection of large hepatocellular carcinoma can be done with safety at a large Western center, and a subgroup of patients will achieve long‐term survival. J. Surg. Oncol. 2013;107:111–117. © 2012 Wiley Periodicals, Inc.